Karakteristik Hak Milik Atas Satuan Rumah Susun Bagi Warga Negara Asing yang Berkedudukan di Indonesia - Mentari Putri Lijaya; Ni Putu Patsana Anggarawati; Dewi Rumaisa (Program Studi Hukum Universitas Pamulang, 2021)
This research is entitled The Characteristics of Ownership Rights of Foreign Citizen Apartment Units domiciled in Indonesia and is based on normative research through the Legislative Approach and Conceptual Approach. In this study, we will discuss the problems between the Laws and Regulations, namely Law No. 5 of 1960 and Law no. 11 of 2020 concerning Work Copyright and other implementing regulations that have no confirmation regarding the subject of Land Rights in the form of Building Use Rights. We already know that foreign citizens are not subjects who can have land rights in the form of building use rights, foreign citizens can only have Apartment Units on State Land or Management Rights with Building Use Rights or Use Rights. Based on these problems, two problem formulations are taken regarding (a) the ratio legis on ownership of Flat Units for Foreign Citizens domiciled in Indonesia; (b) Types of land rights that can be granted to foreign citizens for ownership of apartment units in Indonesia. It is hoped that the preparation of this thesis can produce legal problem solutions for foreign citizens who wish to establish Flats in Indonesia.